Nitrogen Supplying Capacity of Brown Forest Soil under Different Cropping Practices and 0.01 M CaCl2 Soluble Organic Nitrogen - Lazányi, János; Loch, Jakab; Henzsel, István (Acta Agraria Debreceniensis, 2006)
The best known and most remarkable example of continuous production in Hungary is the Westsik’s crop rotation experiment, which was established in 1929, and is still in use to study the effects of organic manure treatment, to develop models, and predict the likely effects of different cropping systems on soil properties and crop yields. In this respect, Westsik’s crop rotation experiment provides data of immediate value to farmers concerning the applications of green, straw and farmyard manure, as well as data sets for scientific research.Although commonly ignored, the release of nitrogen by root and green manure crops has a significant impact on soil organic matter turnover. The design of sustainable nitrogen management strategies requires a better understanding of the processes influencing nitrogen supplying capacity, as the effects of soil organic matter on soil productivity and crop yield are still very uncertain and require further research. In the treatments of Westsik’s crop rotation experiment, nutrients removed from soil through plant growth and harvesting are replaced either by fertilisers and/or organic manure. Data can be used to study the nitrogen supplying capacity of soil under different cropping systems and its effect on the 0.01 M CaCl2 soluble organic nitrogen content of soil.The aim of this paper is to present data on the nitrogen supplying capacity of brown forest soil from Westsik’s crop rotation experiment and to study its correlation with hundredth molar calcium-chloride soluble organic nitrogen. The main objective is to determine the effects of root and green manure crops on the nitrogen supplying capacity of soil under different cropping systems. The nitrogen supplying capacity was calculated as a difference of plant uptake, organic manure and fertiliser supply.The 0.01 M CaCl2 soluble organic nitrogen test has proved reliable for determining the nitrogen supplying capacity of soils. Brown forest soils are low in organic matter and in the F-1 fallow-rye-potato rotation, the nitrogen supplying capacity was 15.6 kg/ha/year. 0.01 M CaCl2 soluble organic nitrogen content was as low as 1.73 mg/kg soil. Roots and green manure increased the nitrogen supplying capacity of soil by more than 100%. This increase is caused by lupine, a legumes crop, which is very well adapted to the acidic soil conditions of the Nyírség region, and cultivated as a green or root manure crop to increase soil fertility.